2014
DOI: 10.1007/s40124-014-0042-z
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Genetic Diagnosis of Autism Spectrum Disorders

Abstract: Autism spectrum disorders (ASD) are a heterogeneous group of neurodevelopmental abnormalities characterized by stereotypical communicative and social impairments, affecting 1 in 88 children in the United States. Both genetic and environmental factors contribute to the etiology of ASD. Autistic traits may be part of features associated with certain syndromes or the sole clinical presentation. Due to extreme heterogeneity and variable expressivity of the condition, clinical diagnosis and management have been cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…The ability to detect genetic causation for autism spectrum disorder (ASD) has improved due to the use of genome wide screening technologies such as chromosomal microarray analysis (CMA) to search for copy number variants (CNVs), and next generation sequencing for single nucleotide variation (Shen and Miller 2014; Talkowski et al 2014; Veenstra-VanderWeele et al 2004). Genetic testing is not considered a diagnostic test for ASD, however, several studies have demonstrated the clinical utility of CMA in terms of changes in clinical management and medical care (Agency for Healthcare Research and Quality (AHRQ) 2014; Beaudet 2013; Coulter et al 2011; Ellison et al 2012; Hayeems et al 2014; Henderson et al 2014; Mefford et al 2012; Riggs et al 2014; Shen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to detect genetic causation for autism spectrum disorder (ASD) has improved due to the use of genome wide screening technologies such as chromosomal microarray analysis (CMA) to search for copy number variants (CNVs), and next generation sequencing for single nucleotide variation (Shen and Miller 2014; Talkowski et al 2014; Veenstra-VanderWeele et al 2004). Genetic testing is not considered a diagnostic test for ASD, however, several studies have demonstrated the clinical utility of CMA in terms of changes in clinical management and medical care (Agency for Healthcare Research and Quality (AHRQ) 2014; Beaudet 2013; Coulter et al 2011; Ellison et al 2012; Hayeems et al 2014; Henderson et al 2014; Mefford et al 2012; Riggs et al 2014; Shen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Platforms such as these are designed to share and present data from genetic testing patients among researchers [5,14,15]. Professionals involved with this project can analyze a bank of test results recorded from patients to identify previously unidentified mutated genes which may contribute to the cause of ASD and other genetic disorders [5,6]. By identifying and recording new candidate genes, the genetic causes that underlie ASD can be more accurately described and better understood [16].…”
Section: Doi: 107243/2054-992x-4-4mentioning
confidence: 99%
“…Several Chromosomal disorders such as Fragile X and Down's Syndrome have also been identified as comorbid for ASD [6]. However, it is believed that roughly half of ASD genetic causes involve de novo, or non-syndromic, mutations [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence continues to increase, from ~1/88 children in 2008 to 1/68 in 2010, according to the Autism and Developmental Disabilities Monitoring Network of the Centers for Disease Control and Prevention [2, 3]. Potential reasons for the increase have been summarized elsewhere and are somewhat debatable [4•]. …”
Section: Introductionmentioning
confidence: 99%